Rapid bioassay of pesticide residues in vegetable samples from Laguna, Philippines - Tipa, E. V. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1997)
A rapid bioassay technique for the detection of pesticide residues was used in screening organophosphates and carbamate insecticides in vegetable samples from Laguna, Philippines.